Cope field - Simpson, T. L. (Flux, 2025)
"A teen baseball star who "has it all"--looks, wealth, and a pro-MLB father--grapples with an impossible choice: reveal his abuse at the hands of his father and risk being separated from his younger brother in the foster care system, or remain silent and risk his brother experiencing that same abuse"--